Using MCMC methods in some application problems - Azhdari, Parvin; Jafarpanahi, Nader; Beitollahi, Arman (International Journal of Scientific World, 2014)
MCMC methods are very important tools for estimating unknown parameters in Bayesian models. Especially in the case of high dimensions. Gaussian mixture model is one of the applications of estimating hyper parameters by MCMC method. Keywords: Gibbs Sampling, Slice Sampling, Metropolis-Hastings Algorithm, Gaussian, Mixture Model.